Association of dengue fever with Aedes spp. abundance and climatological effects - Ángel Francisco Betanzos-Reyes; Mario Henry Rodríguez; Martín Romero-Martínez; Eduardo Sesma-Medrano; Hilda Rangel-Flores; René Santos-Luna (Instituto Nacional de Salud Pública, 2017)
Objective. To analyze the association of dengue fever incidence with Aedes mosquito's abundance, and the effect of climatological and geographical variables, in a region in Morelos State, Mexico. Materials and methods. Weekly data during the period 2010 to 2014 was used. Mosquito abundance was determined using ovitraps. Confirmed dengue cases were obtained from the Epidemiological Surveillance System. Climatic variables were obtained from weather monitoringstations. The correlation between climate variables and ovitraps data was estimated using a multivariate regression model. Results. A correlation of mosquito abundance with dengue fever incidence, and a yearly pattern with seasonal variations were observed. The daily mean temperature, relative humidity and rainfall parameters were associated with mosquito egg abundance. Time lags of three and four weeks between egg counts and dengue fever incidence were observed. Conclusion. Time lags between egg counts and dengue incidence could be useful for prevention and control interventions.